Effect of Sintering Temperature and Soaking Time on the physical and Dielectric Properties of BaTiO3 for Different Ba/Ti Ratio - S. Merzah, Amel; F. Chasib, Khalid (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Recent research has examined the improvement of physical and dielectric properties of BaTiO3 ceramic material by small addition of excess TiO2 or BaCO3. The prepared samples sintered at different temperatures and varying soaking time. The results show that increasing the sintering temperature within 1350°C and soaking time of 10 hrs give better electrical and physical properties, which indicate the reaction is complete at higher temperature and period.